A study on the relationship between factors physical environment comfort and employees' job performance at Pejabat Kesihatan Daerah Setiu / Wan Nur Amirah W. Ibrahim - W. Ibrahim, Wan Nur Amirah (Faculty of Business and Management, 2017)
This paper research was aimed to identify the factors of physical environment comfort that will affect employee's job performance in the workplace at three selected department at Pejabat Kesihatan Daerah Setiu in Terengganu. 66 of the respondents completed the survey questionnaire which was adopted from Amina Hameed and Shehla Amjad (2009). The related and appropriate questionnaire is adapted and adopted from the previous research and few questions are included. The questionnaires will be divided into three sections; Section A, Section B and Section C. This study used simple random technique that the population have been equal and independent chance of being selected to be part of the sample. SPSS version 23 have been used by researcher to analyze the questionnaire in order to conclude the result. This study also need to identify which factors ofphysical environment comfort that most influence employees' job performance. Other than that, this study uses to identify the current problem faced by the employees from physical environment comfort toward their job performance. Most of the respondent at Pejabat Kesihatan Daerah Setiu were female, age between 41 to 50 years old, graduated from university since most of them got Diploma's, and have 11 to 20 years of work experience. The findings showed that the most significant factor that affect employee's job performance was noise and the least significant factor that affect employees' job performance which was lighting. In order to make some improvement to the employees at Pejabat Kesihatan Daerah Setiu, there were several recommendations and suggestions was stated by the researcher.